The Role of Daily Interpersonal Communication among Students of Different Cultures and Countries on Enhancement of Collaborative Learning at Malaysian Universities - Sarwari, Abdul Qahar; Ainol Haryati, Ibrahim; Nor Ashikin, Abdul Aziz (WorldConferences.net, 2014)
Collaborative learning among students of different cultures and countries at university environment is one of the most essential requirements of all modern higher education institutions including Malaysian universities. Therefore, this research project examined various aspects of daily interpersonal communication (IPC) between local and international students of University Malaysia Pahang (UMP), including effects of their daily IPCs on the level of collaborative learning among them. A quantitative survey was conducted as the main method of this study and qualitative interviews were nested to it to enrich the data. The quantitative survey had 220 participants equally from both Malaysian and international students of UMP, and also from both local and international participants, 12 of them were interviewed for the qualitative data. Findings of this study illustrated that daily IPCs between local and international students of UMP enabled both Malaysian and international students to have enough daily collaborative activities at the university environment with students of different cultures and nationalities. Also, findings of this study may highlight the ways for both university students and university policymakers to increase the level of collaborative learning at the university environments. However, further studies on the related issues studies recommended as well.